Drought events determine performance of Quercus ilex seedlings and increase their susceptibility to Phytophthora cinnamomi - Corcobado, Tamara; Cubera, Elena; Juárez, Enrique; Moreno, Gerardo; Solla, Alejandro (Agricultural and Forest Meteorology, 2014)
More frequent weather extremes are expected to occur in the Mediterranean region within the present context of climate change. These extremes could affect forests and plant diseases driven by pathogens. It is hypothesised that simulation of weather extremes during Quercus ilex growth will influence early performance and susceptibility to the invasive oomycete Phytophthora cinnamomi. In 2010, 140 Q. ilex seedlings were subjected to three watering regimes under greenhouse conditions: waterlogging (W), water stress (S) and optimal watering regime for growth (C). During the second vegetative period, conditions were altered to create the following scenarios: WW, WS, SS, SW and CC. After the second vegetative period, plants were artificially infested with P. cinnamomi. Holm oak (Q. ilex) was more sensitive to flooding in the first year of growth than in the second year. The altered scenarios produced plants with a lower fine-to-total root ratio than plants in unaltered scenarios. Plants with the highest growth rates maintained their relatively rapid growth and photosynthetic activity under altered scenarios. However, plants with the highest growth rates became the plants with the lowest growth rates when two consecutive years of drought occurred, indicating a trade-off by Q. ilex in growth investment, observed only if the water stress scenario persists. Seedlings were more sensitive to water shortage than to waterlogging, especially if they encountered a dry scenario during the first year. Exposure to drought events increased seedling mortality rates after P. cinnamomi infection. Waterlogging combined with subsequent water deprivation was the worst scenario when soil was infested with P. cinnamomi, causing 100% mortality of plants.
Keywords: climate change; Drought; Flooding; Invasive pathogen; Oak decline; Weather extremes

Ectomycorrhizal symbiosis in declining and non-declining Quercus ilex trees infected with or free of Phytophthora cinnamomi - Corcobado, Tamara; Vivas, María; Moreno, Gerardo; Solla, Alejandro (Forest Ecology and Management, 2014)
Quercus ilex decline and the presence of the soil-borne pathogen Phytophthora cinnamomi are hypothesised to be associated with shifts in ectomycorrhizal fungi abundance. Soil properties may also influence the relation of this pathogen to ectomycorrhizae. To investigate these associations, 96 Q. ilex declining stands were selected in western Spain and both declining and non-declining trees were sampled. Soil properties (soil depth, Ah horizon thickness, texture, pH, redox potential, soil bulk density and N–NH4+ and N–NO3− concentrations), P. cinnamomi root infections and ectomycorrhizal fungi abundance were assessed. The most dominant ectomycorrhizal morphotypes were Cenococcum geophilum, Tomentella spp. and Russula spp. Lower percentages of non-vital and vital ectomycorrhizal root tips were observed in declining than in non-declining trees. No significant differences in parameters characterising the ectomycorrhizal community between trees infected with or free of P. cinnamomi were observed. However, results indicate that non-mycorrhizal root tips are vulnerable entry points for the pathogen into the tree. More tips were colonised by Russula spp. and other ectomycorrhizal fungi in non-declining infected trees than in declining infected trees. Trees growing on stream banks showed a lower abundance of ectomycorrhizal root tips in fine-textured soils than in coarse-textured soils. Ectomycorrhizal tip abundance was positively related to Ah horizon thickness, irrespective of tree health status. The presence of P. cinnamomi altered relations between ectomycorrhizal abundance and several soil properties. The limited ectomycorrhizal diversity in Q. ilex declining stands and interactions of ectomycorrhizal abundance with soil texture, topography and P. cinnamomi root infections are reported and discussed.
Keywords: Ectomycorrhizae; Iberian dehesa; Invasive pathogen; Oak decline; Soil fertility

Combined effects of soil properties and Phytophthora cinnamomi infections on Quercus ilex decline - Corcobado, Tamara; Solla, Alejandro; Madeira, Manuel A.; Moreno, Gerardo (PLANT AND SOIL, 2013)
The importance of soil properties as determinants of tree vitality and Phytophthora cinnamomi root infections was analysed. The study comprised 96 declining stands in western Spain, where declining and non-declining holm oak (Quercus ilex L.) trees were sampled. Soil properties (soil depth, Ah horizon thickness, texture, pH, redox potential, soil bulk density and N-NH4 (+) and N-NO3 (-) concentrations) and P. cinnamomi infections were assessed. Tree mortality rates increased with low soil bulk densities, which were also associated with more P. cinnamomi-infected trees. Occurrence of infected trees was higher in fine textured soils and in thick Ah horizons. Fine textured soils favoured trees, but with the presence of P. cinnamomi their health status deteriorated. Soil under declining trees had higher N-NO3 (-)/N-NH4 (+) ratio values than under non-declining trees. Additional soil properties changes associated to grazing were not related to decline and P. cinnamomi infections. The implications of P. cinnamomi in holm oak decline and the influence of soil properties as contributors to pathogen activity were demonstrated. Fine soil textures and thick Ah horizons, usually favourable for vigour and vitality of trees growing in the Mediterranean climate, were shown to be disadvantageous soil properties if P. cinnamomi was present. Fine soil textures and thick Ah horizons are frequently related with higher levels of soil moisture, which increase the inoculum of the pathogen and favours root infection. Grazing does not seem to be directly linked to Q. ilex health status or P. cinnamomi root rot.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Nitrogen deposition; Oak decline; Root-rot disease; Silvopastoral systems; Soil compaction; soil texture

Quercus ilex forests are influenced by annual variations in water table, soil water deficit and fine root loss caused by Phytophthora cinnamomi - Corcobado, Tamara; Cubera, Elena; Moreno, Gerardo; Solla, Alejandro (Agricultural and Forest Meteorology, 2013)
Itishypothesised thatmajor reductions intree vitality are related tomarked changes insoilwater content, extremely wet winters followed by dry summers, and the presence of pathogenic organisms which take advantage of this situation. This study helps clarify the role of annual variations in water table, soil water content and ﬁne root abundance in the decline of Quercus ilex forests, with special focus on trees growing in Phytophthora cinnamomi-infested soils. Conducted in western Spain, the study included 5 Q. ilex dehesa stands in which tree water status and soil water dynamic were compared in declining and non-declining trees, and 96 additional stands in which ﬁne root abundance and pathogen assessment were compared in declining and non-declining trees. Declining trees showed signiﬁcantly lower values than non-declining trees for leaf water potential and stomatal conductance. The period of waterlogging (2 months maximum, ﬂuctuating from −0.5 to −4.5m), the soil water content values observed in summer (signiﬁcantly higher in declining trees) and the similar presence of Pythium spiculum in declining and non-declining trees are not sufﬁcient in themselves to explain tree health status. However, ﬁne root density was 16.2% lower in declining than non-declining trees and 42% lower in P. cinnamomi-infected than non-infected trees. Root damage caused by P. cinnamomi in combination with periods of saturated soils favourable for the pathogen but unfavourable for the tree, coupled with small-scale differences in soil water-holding capacity, explain the symptoms and water status of declining trees. The combination of root damage and water stress explained above-ground symptoms of declining trees and will probably determine tree survival.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Oak decline; Open woodlands; Root density; Root-rot disease; Saturated soil; Water deﬁcit